Nigeria Deposit Money Banks’ Credit Administration and the Incidence of Bad Loans: An Empirical Investigation - Afolabi, Babatunde; Oladele, Rotimi; Alli-Momoh, Betty Yemisi; Ayodele, Ademola; Oyamendan, Anthony E (Business, Management and Economics: Research Progress Vol. 3, 2024)
The thrust of this study was to empirically investigate Nigeria’s’ Deposit Money Banks’ Credit Administration and the recurring incidence of Bad Loans. The research work critically examined credit Administration in Nigeria’s Deposit Money Banks, the origin and incidence of bad debts, and the recoveries of Non-Performing Loans and also offered possible ways out of their bad credit and investment portfolio management. The data collected for the study were analysed using tables, simple percentages, and chi-square. A sample of 25 credit officers in each of the four selected banks (Access Bank Plc, First Bank Plc, United Bank of Africa Plc, and Wema Bank Plc) were chosen and questionnaires were administered to them. Based on the information supplied and the analysis of the data gathered from the questionnaires using the chi-square technique, it was found that the unwillingness of banks’ customers’ to provide adequate information and the failure to carry out detailed assessments of the customers’ loan requests results in bad debt, it was also discovered that inadequate securitisation in bank lending has a significant effect on bad debts. The study therefore recommends amongst other things that proper legal documentation be put in place. This would reduce the losses arising from problem loans and minimise the effects of such loans in the form of bad debt provisions, it also suggested that effective monitoring and evaluation are key to avoid the diversion of facilities for unapproved purposes to reduce or forestall the incidence of bad debts in Nigerian Deposit Money Banks.